Mapping subcellular localizations of unannotated microproteins and alternative proteins with MicroID - Na, Zhenkun; Dai, Xiaoyun; Zheng, Shu-Jian; Bryant, Carson J.; Loh, Ken H.; Su, Haomiao; Luo, Yang; Buhagiar, Amber F.; Cao, Xiongwen; Baserga, Susan J.; Chen, Sidi; Slavoff, Sarah A. (Molecular cell, 2022)
Proteogenomic identification of translated small open reading frames has revealed thousands of previously unannotated, largely uncharacterized microproteins, or polypeptides of less than 100 amino acids, and alternative proteins (alt-proteins) that are co-encoded with canonical proteins and are often larger. The subcellular localizations of microproteins and alt-proteins are generally unknown but can have significant implications for their functions. Proximity biotinylation is an attractive approach to define the protein composition of subcellular compartments in cells and in animals. Here, we developed a high-throughput technology to map unannotated microproteins and alt-proteins to subcellular localizations by proximity biotinylation with TurboID (MicroID). More than 150 microproteins and alt-proteins are associated with subnuclear organelles. One alt-protein, alt-LAMA3, localizes to the nucleolus and functions in pre-rRNA transcription. We applied MicroID in a mouse model, validating expression of a conserved nuclear microprotein, and establishing MicroID for discovery of microproteins and alt-proteins in vivo. [Display omitted] •MicroID reveals microproteins and alternative proteins in subnuclear compartments•Alt-LAMA3 is physically and functionally associated with pre-rRNA transcription•MicroID detects unannotated microproteins and alternative proteins in vivo Na et al. develop MicroID, a high-throughput technology to accelerate functional characterization of the trove of recently discovered, unannotated microproteins and alternative proteins. MicroID globally mapped unannotated microproteins and alternative proteins to subcellular localizations in cells and in animals and enabled identification of an alt-protein that regulates pre-rRNA transcription.